A comparative survey of structural characteristics of Finnish university departments - Matthias Deschryvere (The Research Institute of the Finnish Economy (ETLA), 2009)
This descriptive paper analyses structural characteristics of Finnish university departments (FIDs) and benchmarks them against foreign university departments from Scandinavia, the UK and the US (FODs). In the first place the study aims to reveal information on differences in department size. In addition, the analysis pays attention to internationalization, study times and the level of business activities at different university departments. The paper is based on new survey data that distinguish between the national rankings of the university departments and between the department fields. The first finding shows that FIDs are small. This finding seems to hold irrespective of the department field. The second finding shows that the best departments tend to be bigger than the rest. The third result shows that FIDs have low shares of foreign students. Finally the results show that the faculty of Finnish university departments is relatively well involved in business creation.
Keywords: I23; I28; O31; O38; 330; Universities; University departments; Research; Education; Innovation; Hochschule; Forschung; Lehrkräfte; Innovation; Finnland